2016
DOI: 10.1245/s10434-016-5634-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Neutrophil-Lymphocyte and Lymphocyte-Monocyte Ratios Reflect Immune Cell Population Rearrangement in Resectable Pancreatic Cancer

Abstract: BackgroundNeutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and lymphocyte-monocyte ratio (LMR) may serve as a simple index of the immune function. The aim of this study was to investigate the prognostic significance of NLR, PLR, and LMR in patients with resectable pancreatic ductal adenocarcinoma (PDAC) and to verify whether such biomarkers are associated with changes in populations of lymphoid cells.MethodsThe prognostic implications of blood count parameters were evaluated in a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 40 publications
0
75
0
7
Order By: Relevance
“…In the last decade, more and more studies have reported that the systemic inflammatory response is closely related to a poor outcome in many types of tumor . The accumulating increase in NLR and PLR may be caused by peritumoral inflammation produced by a huge amount of cancer cells in patients with advanced cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, more and more studies have reported that the systemic inflammatory response is closely related to a poor outcome in many types of tumor . The accumulating increase in NLR and PLR may be caused by peritumoral inflammation produced by a huge amount of cancer cells in patients with advanced cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, more and more studies have reported that the systemic inflammatory response is closely related to a poor outcome in many types of tumor. [17][18][19][20][21][22] The accumulating increase in NLR and PLR may be caused by peritumoral inflammation produced by a huge amount of cancer cells in patients with advanced cancer. Many studies demonstrate that PLR and NLR are useful biomarkers to predict prognostic outcome in unresectable gastric cancer, resectable gastric cancer, or gastric cancer patients who received chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study described that high NLR and low LMR were associated with unfavorable prognoses of patients with pancreatic cancer. Additionally, both parameters were associated with marked alterations in the subsets of lymphocyte, monocyte, and neutrophil populations, possibly contributing to impaired defense against malignant tumors [10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the systemic inflammatory response (SIR) has been proven to play a key role in cancer progression, development, and metastasis . The neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR), and lymphocyte‐to‐monocyte ratio (LMR) are good markers of the SIR and have shown a significant correlation with clinical outcomes in multiple tumors . In particular, they are simple to derive and economical.…”
Section: Introductionmentioning
confidence: 99%
“…12 The neutrophil-tolymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) are good markers of the SIR and have shown a significant correlation with clinical outcomes in multiple tumors. [13][14][15] In particular, they are simple to derive and economical. However, almost all studies on these factors only focused on a single indicator and their results were inconsistent.…”
Section: Introductionmentioning
confidence: 99%